Prosody of Abuse - K. V. Shulgina; A. V. Pasko (Теория и практика судебной экспертизы, 2021)
The relevance of the study of the prosodic structure of speech acts of abuse is due to the tasks faced by an expert linguist in the study of oral discourse. The present study is experimental; in its course, for the first time, a set of universal and individual prosodic means used when pronouncing a conflict statement with signs of verbal aggression is considered. The purpose of the article is to identify the prosodic characteristics of abuse as an illocutionary act and study the features of suprasegmental units of speech containing invective elements, including those in the structure of utterances not limited by the semantics and pragmatics of abuse. An interdisciplinary approach is applied to analyzing spoken texts based on the appeal to acoustic, auditory, and linguistic analysis methods. The study’s object was unique, authentic utterances: spontaneous sounding speech qualified by the preliminary investigation authorities as a public abuse to a government official. As a result of the study, we identified suprasegmental units that characterize the speakers’ invective speech. The prosodic components of the speech act of abuse within the framework of the utterance include the ascending-descending nature of the frequency of the main tone and increased dynamic characteristics of speech. Statements containing signs of abuse are often carriers of other goals. Prosodic accents in such utterances vary and depend on the leading speech purpose of the utterance. Together with their addresser’s speech goal, the analyzed utterances’ propositional content is manifested by a particular prosodic structure. The intonational model of such statements when solving diagnostic expert problems acts as one of the indicators of a subjective negative assessment, which contributes to identifying a speech act as an abuse.